2015
DOI: 10.1089/pho.2015.3927
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaw: An Autofluorescence-Guided Surgical Approach Performed with Er:YAG Laser

Abstract: Taking into account the advantages of laser therapy and the possible effectiveness of AF in highlighting surgical margins, this approach would probably achieve excellent outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Vescovi et al reported several studies regarding the use of Er:YAG laser to treat BRONJ lesions, showing that Er:YAG seems to represent a high percentage of success, with significantly better results compared with the traditional surgical approaches [15, 39, 44, 45]. …”
Section: Discussionmentioning
confidence: 99%
“…Vescovi et al reported several studies regarding the use of Er:YAG laser to treat BRONJ lesions, showing that Er:YAG seems to represent a high percentage of success, with significantly better results compared with the traditional surgical approaches [15, 39, 44, 45]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that tetracycline-fluorescenceinduced bone fluorescence and fluorescence-guided bone surgery are important tools in the surgical management of MRONJ, as they successfully address the above shortcoming [6][7][8][9][10][11]. The fluorescence technique provides an objectified and reproducible therapeutic approach and enables the transitions between necrotic and non-necrotic bone to be defined during surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Low-level laser therapy has been reported to have superior results in the treatment of bisphosphonate-related osteonecrosis compared with conventional surgical and/or medical therapy (Weber, Camilotti, & Ponte, 2016). Low level laser therapy represents a minimally invasive approach and appears to biostimulate ONJ healing (Altay, Tasar, Tosun, & Kan, 2014;Basso et al, 2014;Porcaro, Amosso, Scarpella, & Carini, 2015;Vescovi, Giovannacci, Otto, et al, 2015). In conclusion, these surgical approaches appear to achieve superior therapeutic results, even in advanced stage ONJ, with very low related morbidity.…”
Section: Optimising Surgical Managementmentioning
confidence: 97%